A Novel and More Efficient Oscillating Foil for Wave-Driven Unmanned Surface Vehicles - Gao, Yan; Xie, Lvcheng; Lam, Tin Lun (Frontiers in Robotics and AI, 2022)
In the wave-driven unmanned surface vehicles (WUSVs), oscillating-foils are the most straightforward and widely used wave energy conversion mechanism, like the wave glider. However, WUSVs usually sail slowly compared with other types of USVs. Improving the thrust of the oscillating foil to increase its speed can help WUSVs improve their maneuverability and shorten the completion of ocean missions. This paper proposed a novel method to enhance oscillating foils' thrust force using asymmetric cross-section shape and asymmetric oscillating motion. The thrust enhancement effect is verified by CFD simulation and pool experiment. The experimental results show that the asymmetric wing can enhance the propulsive force by at least 13.75%. The speed enhancement of WUSVs brought by this enhanced thrust is at least 7.6%, which has also been verified by simulation and sea experiments. The asymmetric foil only needs to make low-cost modifications on the traditional rigid symmetric foil to achieve the desired thrust enhancement effect.